Design and Development of a Web-Based IT Project Management Information System at the WIT.ID Company Using the Scrum and PIECES Methods - Nugraha, Yopi; Maulani, Galih Abdul Fatah; Pangistu, Ryhman Aji (Jurnal Inovasi Bisnis dan Kewirausahaan, 2023)
The IT company, as a pioneer in the development of information technology, utilizes information systems in almost all of its operations, ranging from company management to marketing management. One of the operational aspects of the IT company in conducting its business is client management, in this case, project management. The IT company, WIT.ID, in Bandung, has not yet integrated its project management, resulting in difficulties in allocating programmers for projects due to a lack of data collection. This research aims to understand the project management process, the stages that can be integrated into the system, and its impact on the effectiveness of project management at WIT.ID. This study adopts two methods, namely the analysis of the piece to analyze the capability of the IT project management information system and the Scrum approach to design and build the system. The goal is to enhance the efficiency of IT project management at WIT.ID through the improvement of the information system. The development stages involve analysis, design, implementation, and system testing. The agile Scrum approach is applied to project management. System testing includes black box testing and usability testing, with a feasibility level reaching 86.4%.